Penguatan UMKM Desa Pakel Melalui Implementasi Sosial Media Dan Platform E-Commerce - Bella Mega Riswanti; Siti Ning Farida (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Micro, Small, and Medium Enterprises (MSMEs) are one of the economic sectors that play a crucial role in the economic growth of a country. However, they often face challenges in competing in the increasingly advanced digital era. Therefore, the implementation of digital strategies such as social media and e-commerce platforms has become increasingly relevant to strengthen MSMEs and help them achieve success in the digital economy. This journal concludes by providing recommendations to assist MSMEs in overcoming challenges and maximizing the benefits of implementing social media and e-commerce platforms. These recommendations include training and mentoring in the use of digital technology, the development of targeted marketing strategies, and government policy support to encourage MSME growth through the digital economy.